Sistem Informasi Stok Motor Dan Penjualan Berbasis Web di Dealer Cahaya Sakti Motor Wonogiri - Abdi, Rafsanjani Andyka Baskoro; , Drs. Sujalwo, M. Kom (2017)
Website in this Cahaya Sakti Motors dealer provides convenience for buyers information about available stock and sales information, as well as on this website buyers can directly order the motor and purchased by filling out the form that has been provided on the webafter the buyer ordered. Then the buyer should come to the dealer to make payments just by submit purchase requirement and booking code to the admin or customer service. In addition, this website also allows the dealer to market the motorcycle easyly. This website will make it easier for Customer service tosearch buyers ordering data, so buyers do not need to fill the form again simply by handing order code. This website created using PHP and MySQL programming language, the user interface using HTML, CSS and use the Google Chrome / Mozilla Firefox, and Xampp. At the end of the Research, this applications can help to solving the existing problems in Cahaya Sakti motors at the transaction of salles and purchase either cash or credit, providing information about available motors stock and reports salles and purchase periodically, appropriately and accurately.